Capturing Emerging Trends to Bridge Relevancy Gap Between Academic Delivery of Course on Business Research and Talent Expectation of Re-search Industry: Gaps In Academia and Industry Expectations - Saxena, Nitin; Tiwari, Surendra (Future Science / FSH-PH Publications, 2021)
What is changing in business research in terms of practices and methods? Are the emerging trends in business research valuable enough to be included as essential contents for the course on business research? This research paper aims to troupe a light on the drifts that are likely to sojourn for a significant time and hence are academically must to deliver in classroom session while coaching progression on business research. This paper explores business correlated emergent research practices and tools with an objective to find their suitability from academic standpoint. This paper will uncover the trends that may help students in becoming potentially more suitable and job ready for research industry that offer keys and solutions to businesses and also aids in the advancement the subject substance of course on business research approaches. The global content in this paper creates valuable insight on the basis of exploration of emerging research trends hence this paper shall contribute as a reference material for the imminent forthcoming research interrelated to this topic.